THE ROLE OF POPULATION TRAVEL BEHAVIOUR IN ENSURING SUSTAINABLE URBAN MOBILITY. CASE STUDY - Radu Andrei IOVA; Daniela CREȚU; Oana Roberta CREȚU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The sustainable development of towns is the most important driver of economic and social development and the continuous increase in the number of vehicles has more and more powerful influences on the environment and on the health status of inhabitants in the urban area, due to the polluting matters emissions, noise and road accidents. The lack of integrated planning of transport systems can lead to disruptions in the urban structure of the communities and to strengthening of social exclusion. Starting from these considerations, we initiated the present study in Călărași municipality by which we surveyed the population's opinion on the general problems related to mobility, using the survey - interview and a questionnaire with a number of 15 items, to which a number of 314 persons answered, obtaining information on the number of travels, the problems perceived by the citizens regarding mobility, optimal solutions for improving the situation, the preferred means of transport, if this option would have a sufficient quality, appreciations on public transport, etc., the conclusion being the preference of the citizens for a transport model in which travel behaviour, travel patterns and demands react in time to all socio-economic changes.